Electronic Toys Decrease the Quantity and Lexical Diversity of Spoken Language Produced by Children With Autism Spectrum Disorder and Age-Matched Children With Typical Development - Venker, Courtney E.; Johnson, Jennifer R. (Frontiers in Psychology, 2022)
Many young children with autism spectrum disorder (ASD) have language delays. Play-based interactions present a rich therapeutic context for supporting language and communication development, but electronic toys may compromise the quality of play interactions. This study examined how electronic toys impact the quantity and lexical diversity of spoken language produced by children with ASD and age-matched children with typical development, compared to traditional toys without electronic features. Twenty-eight parent-child dyads (14 per group) played with both electronic and traditional toy sets in a counter-balanced order. Children in both groups talked significantly less and produced significantly fewer unique words during electronic toy play than traditional toy play. Children with ASD and children with typical development appear to take a backseat to electronic toys, decreasing their communicative contributions to play-based social interactions. These findings highlight the importance of considering how toy type can affect parent-child play interactions and the subsequent learning opportunities that may be created. Play-based interventions for children with ASD may be most effective when they incorporate traditional toys, rather than electronic toys.